2017
DOI: 10.1186/s12906-017-1560-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening for antiviral activity of Turkish plants revealing methanolic extract of Rindera lanata var. lanata active against human rotavirus

Abstract: BackgroundHuman rotavirus (HRoV) is the leading cause of severe gastroenteritis in infants and children under the age of five years. No specific antiviral drug is available for HRoV infections and the treatment of viral diarrhea is mainly based on rehydration and zinc treatment. In this study, we explored medicinal plants endemic to Turkey flora as a source of anti-HRoV compunds.MethodsWe performed an antiviral screening on Ballota macrodonta, Salvia cryptantha and Rindera lanata extracts by focus reduction as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…canescens showed moderate in vitro antimicrobial activity [ 14 ], while a methanolic extract of R. lanata var. lanata exerted in vitro antivirus property against a human rotavirus [ 13 ]. The fruits of the widely distributed R. oblongifolia are a rich source of unsaturated fatty acids [ 15 ], similar to the aerial parts, roots, and seeds of the endemic Serbian R. umbellata .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…canescens showed moderate in vitro antimicrobial activity [ 14 ], while a methanolic extract of R. lanata var. lanata exerted in vitro antivirus property against a human rotavirus [ 13 ]. The fruits of the widely distributed R. oblongifolia are a rich source of unsaturated fatty acids [ 15 ], similar to the aerial parts, roots, and seeds of the endemic Serbian R. umbellata .…”
Section: Introductionmentioning
confidence: 99%
“…Rindera graeca and Rindera gymnandra are the only endemic Mediterranean taxa in Greece and Algeria, respectively [12]. Other Rindera species endemic in Turkey (R. dumanii, R. caespitosa, and R. cetineriare) have been used in folk medicine, appreciated for their anti-inflammatory properties [13]. The essential oil from R. lanata var.…”
Section: Introductionmentioning
confidence: 99%
“…All of its species are perennial and adapted to dry climates. Of these, Rindera dumanii , Rindera caespitosa , and the recently identified Rindera cetineriare are endemic to Turkey, where plants from the Rindera genus are traditionally used as an anti-inflammatory medicine [ 5 ]. Essential oil from Rindera lanata var.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a methanolic extract of Rindera lanata var. lanata showed in vitro potential against the human rotavirus, which is responsible for gastroenteritis [ 5 ]. Rindera umbellate , the only endemic Rindera species in Serbia, appeared as a rich source of fatty acids and pyrrolizidine alkaloids (PAs) identified from aerial parts, roots, and seeds in a recent study [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Several authors have reported on plant derived lead molecules efficacious against various stages of viral development. 8,9 Dicrocephala integrifolia is a flowering plant that belongs to the Asteraceae family. 10 In Kenya, it is used in the treatment of skin infections, 11 induction of emesis, purgative, antitumor agent as well as in the management of liver, spleen, kidney, bladder, bone and joint diseases.…”
Section: Introductionmentioning
confidence: 99%